Treatment and long-term outcome in primary distal renal tubular acidosis - Lopez-Garcia, Sergio Camilo; Wühl, Elke (Nephrology, dialysis, transplantation, 2019)
AbstractBackground. Primary distal renal tubular acidosis (dRTA) is a rare disorder, and we aimed to gather data on treatment and long-term outcome.Methods.
Gesehen am 24.09.2019